Música, resiliencia y tradición a través del documental etnográfico. Análisis de Cantadoras. Memorias de vida y muerte en Colombia (Carrillo, 2017) - Mauri Estupiña, David (2025)
Based on a methodology combining film analysis with an interview, this article analyzes Cantadoras. Memories of Life and Death in Colombia (Carrillo, 2017). In it, five women singers from Colombia’s Caribbean and Pacific regions stand as examples of safeguarding the inherited collective memory through music and their daily work, which resists the various consequences of the country’s armed conflict. The article, in this way, approaches the ethnographic documentary, conceived and exercised from the ethical and political point of view, and understands it as an audiovisual tool that allows it to function as a historical document while making subaltern voices visible, whose stories and songs become testimonies of hope, identity, liberation, and social cohesion in their respective communities.